Effect of Graphical Advance Organizers on the Applying Skills of Grade Nine Biology Students - Gulzar, Saadia (JSE, 2025)
In the dawn of twenty-first century, the science content becomes increasingly complex, especially at secondary level, therefore, the need for cognitive tools to enhance comprehension and application becomes crucial. This research study seeks to find out the graphical advance organizers effect on the “applying” skills of grade nine biology students. This study involved two intact groups that is experimental and control. Quasi-Experimental design was used to compare and find out the achievement of the sample groups. The sample size of the study was 57 students. The total duration of study was eight weeks. Graphical advance organizers teaching method is employed for experimental group. Effect of the graphical advance organizers on the applying skills, was found by conducting a biology achievement test comprising of short questions and MCQS for measuring application skills as pre and post test which was taken by both groups at a specified time before and after the intervention. The validation of the tool was done by ten science experts and then reliability was measured by using Cronbach’s Alpha which was 0.79. Data was analyzed by using t-test to determine whether the mean scores of both groups differ significantly or not. It was found from collected data that experimental group has more applying skills as compared to the control group in grade nine biology. Hence, it can be concluded that the use of graphical advance organizers in biology instruction positively influences students’ ability to apply learned concepts. Therefore, it is recommended that Educators should integrate graphical advance organizers into biology teaching strategies to enhance students’ applying skills and overall academic performance.